Numerical Simulation of Basin-edge Effects with Hybrid PSM/FDM Method - Yanyang Chen; Yanbin Wang (Near Surface Geophysics Asia Pacific Conference, 2013)
A 2-D lateral heterogeneous model was constructed to simulate basin-edge effects using PSM/FDM method. Effects of basin-edge geometry and source depth were simulated. PGV of different models are given to illustrate the effects, and it suggests that the basin geometry and the depth of soft sediment play crucial roles in seismic ground motion study for sedimentary basin.